Comparative Risk Assessment of a Hydrogen Refueling Station Using Gaseous Hydrogen and Formic Acid as the Hydrogen Carrier - Kim, Chang Soo; Lee, Younggeun; Kim, Kyeongsu (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
To realize a hydrogen economy, many studies are being conducted regarding the development and analysis of hydrogen carriers. Recently, formic acid has been receiving attention as a potential hydrogen carrier due to its high volumetric energy density and relatively safe characteristics. However, hydrogen refueling systems using formic acid are very different from conventional hydrogen refueling stations, and quantitative risks assessments need to be conducted to verify their safe usage. In this study, a comparative safety analysis of a formic acid hydrogen refueling station (FAHRS) and a gaseous hydrogen refueling station (GHRS) was conducted. Since there is no FAHRS under operation, a process simulation model was developed and integrated with quantitative risk assessment techniques to perform safety analysis. Results of the analysis show that the FAHRS poses less risk than the GHRS, where the vapor cloud explosion occurring in the buffer tank is of greatest consequence. A GHRS poses a greater risk than an FAHRS due to the high pressure required to store hydrogen in the tube trailer. The mild operating conditions required for storage and dehydrogenation of formic acid contribute to the low risk values of an FAHRS. For risk scenarios exceeding the risk limit, risk mitigation measures were applied to design a safe process for GHRS. The results show that the installation of active safety systems for the GHRS allow the system to operate within acceptable safety regions.